Kalanchoe porphyrocalyx var. sambiranensis, a new variety in a Madagascan Kalanchoe (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2019)
Boiteau & Mannoni (1948: 58) proposed recognition of two varieties, apart from the typical one, in the Madagascan Kalanchoe porphyrocalyx (Baker 1883: 142) Baillon (1885: 469) (Crassulaceae subfam. Kalanchooideae). For one of these, the combination K. porphyrocalyx var. sulphurea (Baker 1887: 471) Boiteau & Mannoni (1948: 58) was validly published. However, for the other one their proposed ‘Kalanchoe porphyrocalyx var. sambiranensis Humbert ex Boiteau & Mannoni’ (Boiteau & Mannoni 1948: 58) was not validly published as it lacked a description or diagnosis in Latin, which by then had been one of the requirements for the valid publication of, inter alia, the scientific names of species and infraspecific taxa for 13 years, i.e., since 1 January 1935 (Art. 39.1 of the ICN, Turland et al. 2018). A valid combination for, along with a description of K. porphyrocalyx var. sambiranensis Humbert ex Gideon F.Sm. & Figueiredo, are published here.